mann91malhi
mann91malhi
10-11-2014
Mathematics
contestada
(2((x+1) ^3 – (x+1) ^2 + (x+1)) )+3
Respuesta :
crisforp
crisforp
10-11-2014
( x + 1 )^3 = x^3 + 3x^2 +3x + 1;
(x + 1 )^2 = x^2 + 2x + 1;
=> (2((x+1) ^3 – (x+1) ^2 + (x+1)) )+3 =2( x^3 + 3x^2 +3x + 1 - x^2 -2x - 1 + x + 1 ) + 3 = 2( x^3 + 2x^2 + 2x + 1 ) + 3 =
= 2x^3 +4x^2 +4x + 5.
Answer Link
VER TODAS LAS RESPUESTAS ( 49+ )
Otras preguntas
Consider the equation CO2 → C + O2. What type of reaction is this?
Tammy harvested 6 3/4 pounds of nuts from her pecan tree. If she divides the nuts into 3/4 pound bags, how many bags will she have?
What are the vertex and x-intercepts of the graph of the function below?y= x^2 - 6x-7A. Vertex: (3,-16); Intercepts: x = 1, -7B. Vertex: (3, -16); Intercepts: x
Juanita begins to factor an expression as shown. x2+3x−18=(x+)(x−) What numbers should be placed in the boxes from left to right?
What is the velocity in meters per second of a runner who runs exactly 110 m towards the beach in 72 seconds
Help! Please show work so I can fully understand.
Select the inequality that corresponds to the figure:A.2x + y < 7B. 2x - y < 7C. 2x - y > -7D. None of the above.
How many units long is a segment whose endpoints are (1,2) and (-4,-10)?
Please help! Describe 3D objects. Discuss how to import and export 3D objects and the different file formats used for 3D objects.
graph y=6/5x+1 please include photo of how to graph it and wheee the dots would be